Composition of gall bladder stones associated with octreotide: response to oral ursodeoxycholic acid. Issue 1 (January 1995) - Hussaini, S H; Pereira, S P; Murphy, G M; Kennedy, C; Wass, J A; Besser, G M; Dowling, R H
Abstract : Octreotide, an effective treatment for acromegaly, induces gall bladder stones in 13-60% of patients. Because knowledge of stone composition is essential for studies of their pathogenesis, treatment, and prevention, this was investigated by direct and indirect methods in 14 octreotide treated acromegalic patients with gall stones. Chemical analysis of gall stones retrieved at cholecystectomy from two patients, showed that they contained 71% and 87% cholesterol by weight. In the remaining 12 patients, localised computed tomography of the gall bladder showed that eight had stones with maximum attenuation scores of < 100 Hounsfield units (values of < 100 HU predict cholesterol rich, dissolvable stones). Gall bladder bile was obtained by ultrasound guided, fine needle puncture from six patients. All six patients had supersaturated bile (mean (SEM) cholesterol saturation index of 1.19 (0.08) (range 1.01-1.53)) and all had abnormally rapid cholesterol microcrystal nucleation times (< 4 days (range 1-4)), whilst in four, the bile contained cholesterol microcrystals immediately after sampling. Of the 12 patients considered for oral ursodeoxycholic acid (UDCA) treatment, two had a blocked cystic duct and were not started on UDCA while one was lost to follow up. After one year of treatment, five of the remaining nine patients showed either partial (n = 3) or complete (n = 2) gall stone dissolution, suggesting that their stones were cholesterol rich. This corresponds, by actuarial (life table) analysis, to a combined gall stone dissolution rate of 58.3 (15.9%). In conclusion, octreotide induced gall stones are generally small, multiple, and cholesterol rich although, in common with spontaneous gall stone disease, at presentation some patients will have a blocked cystic duct and some gall stones containing calcium.